Equity Volatility and Corporate Bond Yields in Malaysia - Vijaya Prasad, Dinesh (2010)
This study explores the effect of stock volatility on corporate bond yields in the Malaysian market. Panel data for 2005 to 2010 shows that index returns and macroeconomic variables explain cross-sectional variation in higher-graded corporate bond yields better than credit ratings. This implies that higher grade bonds are less sensitive to information that are firm-specific, and more sensitive to information that is predominantly related to the economy as a whole.